2022
DOI: 10.1093/jnci/djac167
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Pancreatic Cancer in the Long-Term Prospective Follow-Up of Familial Pancreatic Cancer Kindreds

Abstract: Background A family history of pancreatic cancer is associated with increased pancreatic cancer risk. However, risk estimates for individuals in kindreds with an aggregation of pancreatic cancer (>1 relative) are imprecise due to small samples sizes or potentially impacted by biases inherent in retrospective data. Objective Determine the age-specific pancreatic cancer risk as a function of family history using prospect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…Given the intensity of screening paradigms, there is a natural tension in identifying an optimal cohort meeting a threshold whereby the benefits outweigh the risks. A family history of pancreatic cancer is a significant predictor of disease risk, with some series suggesting a six-fold or higher risk compared with the general population 179 , with an increasing number of family members affected with an elevated risk 180 . The risk is also increased for kindred in whom disease onset was particularly young (that is less than 50 years of age) 180 .…”
Section: Hereditary Pancreatic Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…Given the intensity of screening paradigms, there is a natural tension in identifying an optimal cohort meeting a threshold whereby the benefits outweigh the risks. A family history of pancreatic cancer is a significant predictor of disease risk, with some series suggesting a six-fold or higher risk compared with the general population 179 , with an increasing number of family members affected with an elevated risk 180 . The risk is also increased for kindred in whom disease onset was particularly young (that is less than 50 years of age) 180 .…”
Section: Hereditary Pancreatic Cancermentioning
confidence: 99%
“…A family history of pancreatic cancer is a significant predictor of disease risk, with some series suggesting a six-fold or higher risk compared with the general population 179 , with an increasing number of family members affected with an elevated risk 180 . The risk is also increased for kindred in whom disease onset was particularly young (that is less than 50 years of age) 180 . Taken together, the International Cancer of the Pancreas Screening Consortium recommends that screening programmes are implemented for individuals with an estimated lifetime risk of 5 per cent or greater 181 .…”
Section: Hereditary Pancreatic Cancermentioning
confidence: 99%
“…We calculated SIR by dividing the observed PDAC cases in the high-risk group by the expected number of PDAC cases of that group. To calculate the expected number of cases, we used the SEER database [1], matched with age, sex, race, and calendar year for each individual in the high-risk group, as done by Porter et al [24].…”
Section: Methodsmentioning
confidence: 99%
“…Since we used all the PDAC cases in the TriNetX database, but sampled a subset of control patients, we accounted for this imbalance to estimate the PPV and SIR that would be obtained if we had evaluated the model on the full TriNetX population.We calculated SIR by dividing the observed PDAC cases in the high-risk group by the expected number of PDAC cases of that group. To calculate the expected number of cases, we used the SEER database[1], matched with age, sex, race, and calendar year for each individual in the high-risk group, as done by Porter et al[24].…”
mentioning
confidence: 99%
“…MicroRNAs (miRNAs) are a kind of single-stranded noncoding RNA composed of 18–24 nucleotides, which participate in the regulation of many physiological processes by controlling mRNA translation. A great deal of research evidence identify that the imbalance of specific miRNA expression is closely related to the occurrence of cancer or other pathological conditions, so some specific miRNAs have been identified as biomarkers for cancer diagnosis, therapy, and prognosis. Pancreatic ductal adenocarcinoma (PDAC) is considered to be one of the mortal neoplasms with the worst prognosis, which is difficult to diagnose at an early stage. Previous studies have demonstrated that miRNA-196a is significantly upregulated but miRNA-217 is markedly downregulated in PDAC, while miRNA-217 was highly expressed and miRNA-196a was low expressed in normal pancreas . Therefore, exploring simultaneous ultrasensitive detection and precise colocalization imaging of miR-217 and miR-196a in living cells holds immense importance in the early diagnosis of pancreatic cancer and ensure detection specificity.…”
Section: Introductionmentioning
confidence: 99%